Analisis Kualitas Pelayanan Publik Di Bidang Perlindungan Anak Terlantar Pada Dinas Sosial Kabupaten Probolinggo - Mastina Maksin; Sisca Ratna Vidyanti; Renny Candradewi Puspitarini; Verto Septiandika (Universitas Mbojo Bima, 2026)
Public services are one of the government’s responsibilities in meeting the basic needs of the community, including providing protection for neglected children. Neglected children are a vulnerable group that requires special attention and care from the government through various social service programs. This study aims to analyze the quality of public services in the field of protection for neglected children at the Probolinggo Regency Social Services Office. It employs a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and documentation involving relevant parties within the Probolinggo Regency Social Services Office as well as service recipients. This indicates that the quality of public services for the protection of neglected children at the Probolinggo Regency Social Services Office can be analyzed through several dimensions of service quality, namely tangibles (physical evidence), reliability, responsiveness, assurance, and empathy. In general, the services provided have been functioning quite well, as evidenced by the availability of service facilities, clear service procedures, and the staff’s efforts to provide assistance and protection to neglected children. However, there are still several challenges, such as limited human resources, a lack of supporting facilities and infrastructure, and budget constraints, which hinder the optimization of services. While the quality of public services in the area of protection for neglected children at the Probolinggo Regency Social Affairs Office has been implemented fairly well, there is still room for improvement in several areas so that the services provided can be more optimal, effective, and targeted. quality of public services, protection of neglected children, Probolinggo Regency Social Services Agency.